Pajak daerah, Retribusi Daerah, dan Dana Alokasi Khusus terhadap Belanja Modal Provinsi Se-sumatera - Khairul Umri; Rita Martini; Rosy Armaini (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The purpose of this study was to test and analyze the effect of local taxes, local levies, special allocation funds on capital expenditures of the Sumatra provincial government in 2018-2022. Used for 10 provinces in Sumatra. For five years, fifty samples were used. The test analysis methods used are Measurement model evaluation, convergent validity test, significance test, R-square testing and F-square testing. The results of this study indicate that local taxes, local levies, and special allocation funds have a positive effect on capital expenditure.